2016
DOI: 10.4067/s0718-16202016000300011
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF FOLIAR BORON SPRAYING ON THE FRUIT FEATURES OF BRIGITTA AND LEGACY HIGHBUSH BLUEBERRY (Vaccinium corymbosum) CULTIVARS

Abstract: is associated with reproductive and antioxidant metabolism in plants, and in southern Chile, the deficiency of this micronutrient is ameliorated through foliar applications that are a part of agricultural management, thus ensuring the productivity of crops including highbush blueberry (Vaccinium corymbosum L.). However, the appropriate B dosage for this species is unknown, so the aim of this study was to evaluate foliar B application on fruit quality in highbush blueberry in southern Chile. During the 2014-201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…To ensure an adequate B supply, agronomic efforts are carried out by traditional soil application, fertigation, and foliar spraying of soluble B sources, particularly during reproductive stages, both in conventional and organic highbush blueberry production. However, excessive B addition by farmers could cause environmental risks and counteract the nutritional properties of marketable berries, especially considering the narrow range of optimal B concentrations in plants (Wójcik 2005;Saadati et al 2013;Meriño-Gergichevich et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure an adequate B supply, agronomic efforts are carried out by traditional soil application, fertigation, and foliar spraying of soluble B sources, particularly during reproductive stages, both in conventional and organic highbush blueberry production. However, excessive B addition by farmers could cause environmental risks and counteract the nutritional properties of marketable berries, especially considering the narrow range of optimal B concentrations in plants (Wójcik 2005;Saadati et al 2013;Meriño-Gergichevich et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that the nutrient status of fruit crops may depend on B supply, the genotypic constitution, planting age, and the sampling moment during the season (Strik and Vance 2015;Wang et al 2015;Meriño-Gergichevich et al 2016). Previously, Meriño-Gergichevich et al (2017) reported changes in macronutrient composition and increased radical scavenging activity (RSA) in the leaves and roots of highbush blueberry plants grown under excessive B concentration (> 400 μM).…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, rational foliar fertilization has proved to be an important tool considering nutrient-deficient soils caused by natural or anthropogenic factors, and phenological stage of crops, with advantages such as quick plant responses, lower concentrations of added nutrients, uniformity, and less groundwater contamination (Keshavarz et al, 2011;Fernández and Brown, 2013;Zhang et al, 2016). Previous studies have emphasized the synergistic effect of combined B and Zn applications in several cropped species (Keshavarz et al, 2011;Mukhopadhyay and Mondal, 2015;Davarpanah et al, 2016;Alidust et al, 2020), particularly as supplementation program frequently recommended during springtime in fruit orchards (Solar and Stampar, 2000;Keshavarz et al, 2011;Meriño-Gergichevich et al, 2016).…”
Section: Effects Of Different B and Zn Spraying Programs On Hazelnut Leavesmentioning
confidence: 99%
“…Indeed, low B (0.5-1.0 mg kg −1 ) and Zn (<1.0 mg kg −1 ) concentrations in Andisols have been widely reported by Rodríguez and Tomic (1984), Rodríguez et al (2001), and Bonomelli et al (2003). Boron and Zn deficiencies are undoubtedly becoming important limiting factors for normal growth and development of fruit crops (Davarpanah et al, 2016;Meriño-Gergichevich et al, 2016) affecting metabolic pathways and resulting in reduced shoot growth, fruit set, and quality, as well as mineral and nutritional status of fruits (Özenç and Bender Özenç, 2015;Davarpanah et al, 2016;Marschner 2012). In this context, for hazelnuts planted in Southern Chile, leaf chemical analyses of the Laboratory of Soil and Plants and Scientific and Technological Bioresource Nucleus BIOREN-UFRO (www.bioren.ufro) at the Universidad de La Frontera have reported among 16-63 and 26-41 mg kg −1 DW (dry weight) of hazelnut cultivar Tonda di Giffoni (TDG) for B and Zn concentrations, respectively.…”
Section: Introductionmentioning
confidence: 97%
“…El arándano es una especie del género Vaccinium originaria de Norteamérica, descrita como un arbusto de baja altura, de hoja simple, ovada a lanceolada y caduca (Muñoz, 2015), cuyo fruto es una baya esférica de coloración desde azul claro hasta negro azulado (Vaccinium corymbosum), con un calibre que fluctúa entre los 0,7 a los 1,5 cm (Stückrath y Petzold, 2007;Külkamp et al, 2014). En Chile, el arándano fue introducido en la década de los ochenta (Bañados, 2006, citado por Pannunzio et al, 2011, siendo su cultivo impulsado como parte de la estrategia de mercado de diversificación de las actividades productivas de la agricultura chilena (Meriño-Gergichevich et al, 2016). Su adaptabilidad a las condiciones geográficas de la zona centro sur de país, lo ha convertido en uno de los productos relevantes de la industria frutícola nacional, registrándose un aumento considerable de la superficie cultivada desde su introducción hasta la actualidad, llegando a ocupar la tercera posición mundial en superficie plantada (Retamales et al, 2014).…”
Section: Introductionunclassified